The bird king ebook A novel. - Wilson, G. Willow (2022)
One of NPR's 50 Best Science Fiction and Fantasy Books of the Decade: A fifteenth-century palace mapmaker must hide his powers in the time of the Inquisition . . . Award-winning author G. Willow Wilson's debut novel Alif the Unseen was an NPR and Washington Post Best Book of the Year and established her as a vital American Muslim literary voice. Now she delivers The Bird King , an epic journey set during the reign of the last sultan in the Iberian peninsula at the height of the Spanish Inquisition. Fatima is a concubine in the royal court of Granada, the last emirate of Muslim Spain. Her dearest friend, Hassan, the palace mapmaker and the one man who doesn't leer at her with desire, has a secret—he can draw maps of places he's never seen and bend the shape of reality. When representatives of the newly formed Spanish monarchy arrive to negotiate the sultan's surrender, Fatima befriends one of the women, not realizing that she will see Hassan's gift as sorcery and a threat to Christian Spanish rule. With their freedoms at stake, what will Fatima risk to save Hassan and escape the palace walls? As the two traverse Spain with the help of a clever jinn to find safety, The Bird King asks us to consider what love is and the price of freedom at a time when the West and the Muslim world were not yet separate. "Wilson has a deft hand with myth and with magic, and the kind of smart, honest writing mind that knits together and bridges cultures and people." —Neil Gaiman, author of Norse Mythology "A triumph . . . one of the best fantasy writers working today." — BookPage "A treasure-house of a novel, thrilling, tender, funny, and achingly gorgeous. I loved it." —Lev Grossman, author of the Magicians trilogy